Applied plastics engineering handbook processing and materials - Kutz, Myer (PDL handbook series., 2011)
A practical reference for all plastics engineers who are seeking to answer a question, solve a problem, reduce a cost, improve a design or fabrication process, or even venture into a new market. Applied Plastics Engineering Handbook covers both polymer basics - helpful to bring readers quickly up to speed if they are not familiar with a particular area of plastics processing - and recent developments - enabling practitioners to discover which options best fit their requirements. Each chapter is an authoritative source of practical advice for engineers, providing authoritative guidance from experts that will lead to cost savings and process improvements. Throughout the book, the focus is on the engineering aspects of producing and using plastics. The properties of plastics are explained along with techniques for testing, measuring, enhancing and analyzing them. Materials and additives are described as well as their characteristics and effects. The technologies and machinery used in processing operations are covered with reference to product design. And recent developments in a cross-section of applications demonstrate in a pragmatic way, the opportunities as well as the limitations of plastics. Practical introductions to both core topics and new developments make this work equally valuable for newly qualified plastics engineers seeking the practical rules-of-thumb they don't teach you in school, and experienced practitioners evaluating new technologies or getting up to speed on a new field. The depth and detail of the coverage of new developments enables engineers and managers to gain knowledge of, and evaluate, new technologies and materials in key growth areas such as biomaterials and nanotechnology. This highly practical handbook is set apart from other references in the field, being written by engineers for an audience of engineers and providing a wealth of real-world examples, best practice guidance and rules-of-thumb.